KAJIAN MINAT MASYARAKAT TERHADAP PARIWISATA ALTERNATIF DAN WISATA PEDESAAN MELALUI GOOGLE TRENDS - Zahrotun Satriawati; Hendi Prasetyo; Novi Irawati (Kepariwisataan: Jurnal Ilmiah, 2023)
The development of tourism during the Covid-19 pandemic experienced a transition towards alternative tourism. Public interest in rural-based alternative tourism is a choice of travel in the search aspect through the Google search engine. This can be known from search results by analyzing Google Trends. Google Trends is a tool that can be used to collect and analyze information about web-based information search behavior. The purpose of this study is to examine the development trend of searching for types of tourism related to alternative tourism and rural tourism in Indonesia using Google Trends Analysis. The search method using Google Trends was carried out on data for a period of 2 years from 2020 to 2022 with the keywords "pariwisata alternatif" and "wisata pedesaan". Google Trends data is available in volume format or known as relative search volume (RSV) with a value of 0-100. The analysis was carried out by reading the visual representation of Relative Search Volume (RSV) data images and comparing it with the results of previous research on the development of tourism, alternatives and rural tourism in Indonesia. The results show that the trend of wisata pedesaan in information search results dominates when compared to pariwisata alternatif.